PENDEKATAN TAFSIR AL-QURAN DAN PERKEMBANGANNYA DALAM SEJARAH - Karim, Abdullah (Jurnal Ilmu Ushuluddin, 2015)
In the half second of 20th century, methodology of tafsir had developed very significant. Muhammad Husain al-Dzahabiy from Egypt, when he wrote his manuscript for his inauguration as a professor, al-TafsÃ®r wa al-MufassirÃ»n,in 1946, stated that there were three approaches of commentary of QurâÃ¢n. They were al-MaâtsÃ»r, al-MaâqÃ»l, andÂ al-IsyÃ¢riy. Many people of the âulÃ»mul-QurâÃ¢n scholars quoted his discovery then. Next, in 1966, the work ofÂ Muhammad al-Fadhil bin âAsyur from Tunisia, entitled al-Tafsir wa Rijaluh, had been publicated. In this work, heÂ stated a little bit different from the previous that there were three approaches of commentary of QurâÃ¢n; al-Atsariy, al-Nazhariy, and al-Naqdiy. His work have been important reference for the scholars of âulÃ»mul-QurâÃ¢n then. Thiswriting is going to discuss about approaches in the commentary of QurâÃ¢n as mentioned above.